AI chatbots for education - Oak, Soe Khant (Nanyang Technological University, 2024)
The rapid development of Large Language Models (LLMs) has transformed the landscape of education, enabling students and educators to leverage AI tools for enhanced learning experiences. However, the reliance on individual AI tools have caused a decline in collaborative learning and increase in knowledge silos during group projects. This project presents GroupGPT, an AI-powered learning assistant designed to facilitate collaborative group work among students. Unlike individual usage of tools like ChatGPT, GroupGPT allows students to interact with AI models collectively, fostering group discussions while improving access to educational resources. The application supports realtime chat, document management, and several AI query modes, such as PDF queries and Retrieval-Augmented Generation (RAG).